Preparation of Teaching Book Based on Integrative Approach in - Baiq Widia Nita Kasih (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
Arabic learning in Indonesia is divided into two institutions that is Arabic